Anxiety levels of students facing exam situations: CAEX questionnaire - Sairitupac Santana, Sofia (2020)
The purpose of the study was to compare the anxiety levels of fifth-year high school students from two private educational institutions. The study is of a quantitative approach, type of substantive study, comparative descriptive level and non-experimental cross-sectional design, the population consisted of 400 students from two private schools, the reference students are in the fifth year of secondary school. The instrument used was the Test Anxiety Problem Assessment Questionnaire (CAEX). Questionnaire specifically developed to collect the variety of motor, verbal, cognitive or physiological responses that usually accompany these problems, together with the most frequent type of examinations. As a consequence of the study, we can conclude according to the value of the Mann Whitney U statistic with p value <0.05, it indicates that there are significant differences in the anxiety levels of the students of the two private educational institutions under study, concluding that the students of the two private educational institutions present high levels of anxiety before the exams, a situation that can affect their emotional state that are even dangerous to health (Serious presence of anxiety).